Catalpol ameliorates endothelial dysfunction and inflammation in diabetic nephropathy via suppression of RAGE/RhoA/ROCK signaling pathway. (1st October 2021) - Shu, Anmei; Du, Qiu; Chen, Jing; Gao, Yuyan; Zhu, Yihui; Lv, Gaohong; Lu, Jinfu; Chen, Yuping; Xu, Huiqin
Abstract: Catalpol is an iridoid glycoside compound isolated from the root of Rehmannia glutinosa, which has been reported to be a promising candidate for the treatment of diabetic diseases. The present study aimed at investigating the effects and potential mechanism of catalpol on endothelial dysfunction and inflammation in diabetic nephropathy (DN). We constructed DN mice and advanced glycation end products (AGEs)-induced mouse glomerular endothelial cells (mGECs) injury model. The results demonstrated that catalpol effectively improved renal pathology and decreased levels of urine protein, serum creatinine, and blood urea nitrogen in DN mice. Catalpol significantly reduced endothelial dysfunction and inflammatory infiltration of macrophages in DN mice and AGEs-induced mGECs. To further study the protective mechanism of catalpol, we transfected DN mice with recombinant adeno-associated virus expressing receptor of AGEs (RAGE) and intervened AGEs-induced mGECs with inhibitors. Catalpol reversed endothelial dysfunction and inflammation aggravated by RAGE overexpression in DN mice. Meanwhile, catalpol significantly inhibited the RAGE/Ras homolog gene family member A (RhoA)/Rho-associated kinase (ROCK) pathway in DN mice with RAGE overexpression. Moreover, the combination of catalpol with inhibitors of RAGE, RhoA and ROCK exerted stronger anti-endothelial dysfunction and anti-macrophage infiltration effects on AGEs-induced mGECs compared with catalpol alone. In short, this study indicated that catalpol could ameliorate endothelial dysfunction and inflammation via suppression of RAGE/RhoA/ROCK pathway, hereby delaying the progression of DN. Graphical abstract: Image 1 Highlights: Catalpol ameliorates glomerular endothelial dysfunction and inflammation in DN. RAGE overexpression in DN mice aggravates glomerular endothelial dysfunction and inflammatory infiltration of macrophages. Catalpol inhibits AGEs-RAGE and its downstream RhoA/ROCK signaling pathway.